2018
DOI: 10.1111/nan.12451
|View full text |Cite
|
Sign up to set email alerts
|

Review: Animal models of acquired epilepsy: insights into mechanisms of human epileptogenesis

Abstract: A. J. Becker (2018) Neuropathology and Applied Neurobiology 44, 112-129 Animal models of acquired epilepsy: insights into mechanisms of human epileptogenesisIn many patients who suffer from epilepsies, recurrent epileptic seizures do not start at birth but develop later in life. This holds particularly true for epilepsies with a focal seizure origin including focal cortical dysplasias and temporal lobe epilepsy (TLE). TLE most frequently has its seizure onset in the hippocampal formation. Hippocampal biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 207 publications
1
119
0
9
Order By: Relevance
“…The degree of lesion in the hippocampus is associated with neuronal loss and astrogliosis that correlated with seizure severity. that astrocytic dysfunction would strengthen the release of glutamate and intensify Wetherington et al demonstrated neuronal excitability, thus leading to seizures . Our results illustrated that mice with fewer seizures had less severe neuronal atrophy and astrogliosis in their hippocampus and the hilus of DG, implying that GR could modulate SE formation and contribute to seizure maintenance.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The degree of lesion in the hippocampus is associated with neuronal loss and astrogliosis that correlated with seizure severity. that astrocytic dysfunction would strengthen the release of glutamate and intensify Wetherington et al demonstrated neuronal excitability, thus leading to seizures . Our results illustrated that mice with fewer seizures had less severe neuronal atrophy and astrogliosis in their hippocampus and the hilus of DG, implying that GR could modulate SE formation and contribute to seizure maintenance.…”
Section: Discussionsupporting
confidence: 53%
“…that astrocytic dysfunction would strengthen the release of glutamate and intensify Wetherington et al demonstrated neuronal excitability, thus leading to seizures. [24][25][26] Our results illustrated that mice with fewer F I G U R E 3 A, The regulatory effect of Gastrodiae Rhizoma (GR) and carbamazepine (CBZ) on p-mTOR expression. Data were shown as mean ± SD; negative absorbance was not excluded from the analysis.…”
Section: Discussionmentioning
confidence: 66%
“…The theory of "master regulators" controlling the transcriptional dynamics of genes involved in epileptogenesis is attractive because this would mean that blocking these transcriptional regulators could be particularly powerful in exerting antiepileptogenic and disease-modifying effects. Numerous "master regulator candidates," comprising transcriptional activators and repressors, have been suggested (for review, see Becker, 2018). However, only few reports so far have demonstrated the regulation of more than one gene encoding a protein integrally involved in the processes underlying epileptogenesis by a single transcription factor (TF) (McClelland et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studying early EPG in human patients is extremely difficult, simply because the epilepsy is typically only detected after the FSS. Therefore, work on early EPG is typically restricted to animal models [4]. Furthermore, early EPG can comprise a complex cascade of changes to the brain after the initial brain insult and this cascade may strongly depend on the type of brain insult.…”
Section: Introductionmentioning
confidence: 99%